Improving Mekong water resources investment and allocation choices - Dore, J.; Molle, Francois; Lebel, L.; Foran, T.; Lazarus, Kate (CGIAR Challenge Program on Water and Food, 2010)
The CPWF Project PN67 “Improving Mekong Water Allocation” was a key, collaborative activity of the Mekong Program on Water, Environment and Resilience (M-POWER). The goal of contributing to water allocation policy and practice which results in a more optimal and equitable use of water by society has been pursued by research across the Mekong Region and active engagement with policymakers. The project team have examined the use of a wide range of decision-support tools, in many decision-making arenas. In doing so, they have sought to understand decision contexts and drivers.